2020
DOI: 10.1002/glia.23953
|View full text |Cite
|
Sign up to set email alerts
|

A reporter cell system for the triggering receptor expressed on myeloid cells 2 reveals differential effects of disease‐associated variants on receptor signaling and activation by antibodies against the stalk region

Abstract: The triggering receptor expressed on myeloid cells 2 (TREM2) is an immune receptor expressed on myeloid‐derived cell types. The extracellular immunoglobulin‐like domain of TREM2 binds anionic ligands including Apolipoprotein E and Amyloid‐β. The transmembrane domain interacts with its adaptor protein DAP12/TYROBP that is responsible for propagation of downstream signaling upon ligand interaction. Several sequence variants of TREM2 have been linked to different neurodegenerative diseases including Alzheimer's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The negatively stained sample was then examined by using Talos L120C (Thermo Fischer Scientific) at an acceleration voltage of 120 kV imaged with 4 k  4 K Ceta CMOS camera at x45,000. Representative images are shown in Figure S1 high glucose [4.5 g/L], phenol red, sodium pyruvate additive, 10 mM HEPES), supplemented with 10% heat-inactivated fetal calf serum (FCS), 1% penicillin and streptomycin (P/S) solution, and 100 μg/ml hygromycin in incubators maintained at 37 C and 5% CO 2 (Ibach et al, 2021). Using the QuikChange-II kit (Agilent Technologies), site directed mutagenesis was carried out according to the manufacturer's instructions in order to introduce the stop codon at aa158 of full length TREM2 construct.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 3 more Smart Citations
“…The negatively stained sample was then examined by using Talos L120C (Thermo Fischer Scientific) at an acceleration voltage of 120 kV imaged with 4 k  4 K Ceta CMOS camera at x45,000. Representative images are shown in Figure S1 high glucose [4.5 g/L], phenol red, sodium pyruvate additive, 10 mM HEPES), supplemented with 10% heat-inactivated fetal calf serum (FCS), 1% penicillin and streptomycin (P/S) solution, and 100 μg/ml hygromycin in incubators maintained at 37 C and 5% CO 2 (Ibach et al, 2021). Using the QuikChange-II kit (Agilent Technologies), site directed mutagenesis was carried out according to the manufacturer's instructions in order to introduce the stop codon at aa158 of full length TREM2 construct.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Using the QuikChange-II kit (Agilent Technologies), site directed mutagenesis was carried out according to the manufacturer's instructions in order to introduce the stop codon at aa158 of full length TREM2 construct. The generation of stable cell line was described previously (Ibach et al, 2021).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the potential therapeutic impact of targeting TREM2, we decided to generate single-chain variable antibody fragments (scFvs) against the human TREM2 ectodomain with which to study TREM2 structure and function. Agonist antibodies have already been reported in recently published work (Ellwanger et al, 2021;Fassler et al, 2021;Ibach et al, 2021;Price et al, 2020;Schlepckow et al, 2020;Wang et al, 2020). The group of Schlepckow have shown that a full-length antibody specific to mouse TREM2 can decrease shedding and activate TREM2 signaling in vitro, and also lead to a significant reduction in amyloid plaques in 6-month-old amyloid-beta precursor protein knockin mice (Schlepckow et al, 2020).…”
Section: Articlementioning
confidence: 99%